Kualitas Organoleptik Kue Bugis Hitam Berbahan Dasar Tepung Kacang Gude Sebagai Substitusi Tepung Ketan Hitam - Sudiarta, Ngakan Putu; Prasanti, Kadek Dita (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
This study explores the utilization of pigeon pea flour in Bugis cake production and its evaluation through organoleptic testing. Pigeon pea is recognized for its high protein and carbohydrate content. The research incorporates three samples: A (100% pigeon pea flour), B (1:2 ratio of glutinous rice flour to pigeon pea flour), and C (2:3 ratio of glutinous rice flour to pigeon pea flour). The primary objective is to assess the quality of Bugis cakes made using pigeon pea flour. Data collection methods encompass experimentation, organoleptic testing, panelists, questionnaires, and Likert scales. Qualitative descriptive analysis is employed for data analysis. The organoleptic testing results, evaluated using the Likert scale, indicate that sample A achieves an average score of 65% (